2021
DOI: 10.3389/fmed.2021.595522
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Microbiome in Interstitial Lung Diseases

Abstract: There are trillions of microorganisms in the human body, consisting of bacteria, viruses, fungi, and archaea; these collectively make up the microbiome. Recent studies suggest that the microbiome may serve as a biomarker for disease, a therapeutic target, or provide an explanation for pathophysiology in lung diseases. Studies describing the impact of the microorganisms found in the respiratory tract on lung health have been published and are discussed here in the context of interstitial lung diseases. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 76 publications
(80 reference statements)
1
34
0
1
Order By: Relevance
“…Thus, there is a close interaction between respiratory and intestinal diseases [17,18], which is de ned as gut-lung axis. To our best knowledge, the micro ora in gut and lung are rather complicated, which play important roles in the pathogenesis of pulmonary and intestinal diseases through the gut-lung axis [19][20][21]. In previous studies, disturbance of microorganism was closely associated with the progression and prognosis of lung cancer [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there is a close interaction between respiratory and intestinal diseases [17,18], which is de ned as gut-lung axis. To our best knowledge, the micro ora in gut and lung are rather complicated, which play important roles in the pathogenesis of pulmonary and intestinal diseases through the gut-lung axis [19][20][21]. In previous studies, disturbance of microorganism was closely associated with the progression and prognosis of lung cancer [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a study of human alveolar epithelial cells showed that exposure to PHMG and PGH elevates the level of the epithelial–mesenchymal transition (EMT)-related protein, an indicator of fibrotic response [ 10 ]. Additionally, there is a possibility for the role of microbiome advances in lung injuries and idiopathic pulmonary fibrosis (IPF), which may potentially link to the environmental exposures [ 26 , 27 , 28 ]. Taken together, it seems plausible that HD-induced inflammation and mRNA expression of fibronectin might trigger a wound-healing response, causing epithelial cells to be stiff and thickened, eventually leading to pulmonary fibrosis, which is identical to the features of HDLI cases.…”
Section: Discussionmentioning
confidence: 99%
“…Over the notable and wide evidences on gut microbiota, lung has its own "microbiota" [57]. While in the gut Bacteroidetes and Firmicutes are predominant, Bacteroidetes, Firmicutes and Proteobacteria are the most represented in the lung [58].…”
Section: Potential Gut Microbiota Modulation In Critically Ill Patient With Sars-covmentioning
confidence: 99%
“…The "gut-lung axis" is a pathophysiological bidirectional model involved in the pathogenesis of several pulmonary diseases. Specifically, endotoxins (e.g., bacterial lypopolisaccharide (LPS)), microbial metabolites of gut origin can reach the lung through the bloodstream, bringing to the inflammation of the lung tissues and, in a circle, back to the intestine [58]. Thus, it is conceivable that the novel SARS-Cov2 might affect the gut microbiota such as in other interstitial and non-interstitial lung diseases [59].…”
Section: Potential Gut Microbiota Modulation In Critically Ill Patient With Sars-covmentioning
confidence: 99%
See 1 more Smart Citation